Mean platelet volume and mean platelet volume/platelet count ratio in infective endocarditis. (December 2014) - Cho, Sun Young; Jeon, You La; Kim, Weon; Kim, Woo-Shik; Lee, Hee Joo; Lee, Woo-In; Park, Tae Sung
Abstract Infective endocarditis (IE), an infection of the endocardial surface, frequently leads to life-threatening complications, such as thromboembolism due to platelet activation. We investigated the mean platelet volume (MPV) in Korean patients with IE and the serial changes thereof, in comparison with other laboratory parameters. We analyzed 248 MPV results from 22 patients diagnosed with IE in our hospital between January 2011 and April 2012. MPV was measured with an Advia 2120 (Siemens Healthcare Diagnostics, Tarrytown, NY) using EDTA-containing tubes. The mean MPV differed significantly between the patient and control groups, 8.74 vs. 7.96 fl, respectively. In addition, the platelet count and MPV/platelet count ratio were significantly decreased in the patient group. The total platelet mass and platelet size in IE might be increased. Further studies should examine more patients to verify the changes in the MPV and MPV/platelet count ratio in IE and assess in greater detail the relationship between MPV and thrombotic complications caused by platelet activation.